Mycobacterium phocaicum and Mycobacterium avium‐intracellulare in a patient with hot tub lung. Issue 1 (14th January 2015) - Wethasinghe, James; Hotu, Sandra; Taylor, Susan; Anderson, Graeme; Wong, Conroy
Abstract A 77‐year‐old woman who used her spa pool at least twice a day to relieve pain from osteoarthritis, developed progressive breathlessness, impaired pulmonary function, and radiographic changes consistent with hypersensitivity pneumonitis‐like lung disease. Mycobacterium avium‐intracellulare complex (MAC) was cultured from bronchoalveolar lavage fluid. Transbronchial biopsies revealed non‐necrotizing granulomatous inflammation. Sputum and spa pool water cultured Mycobacterium phocaicum but not MAC. She stopped using the spa pool and was treated with oral prednisone, which led to symptomatic, pulmonary function, and radiographic improvement. This is the first case of hypersensitivity pneumonitis‐like granulomatous lung disease associated with exposure to M. phocaicum in spa pool water.